Good Governance Practices of COBIT 2019 and ITIL v4 for Sustainable Service Management in Museum Electronic-Based Government System - Fauzia Dhiyaa' Farros; Dinar Mutiara Kusumo Nugraheni (Scientific Journal of Informatics, 2026)
Purpose: Good governance practices in transparency, accountability, responsibility, fairness, and stakeholder participation are core principles that ensure governance mechanisms are not merely procedural, but also creates a sustainable service management environment that aligns governance conditions with public interests. Methods/Study design/approach: Through the integration of COBIT 2019 and ITIL v4 frameworks, along with structured staff interviews, service performance analysis, and direct operational observations, several important domains emerged, indicating the need for management development. Result/Findings: The results show that several COBIT 2019 domains, APO07 (Managed Human Resources), DSS01 (Managed Operations), BAI03 (Managed Solutions Identification and Build), EDM02 (Ensured Benefits Delivery), and MEA01 (Managed Performance and Conformance Monitoring) and ITIL v4 domains, Information Security Management, Organizational Change Management & Workforce, Continual Improvement require immediate improvement with the Capability Index  scored 46.875% classified as Partially Achieved (15–49%) and classified in Level 2 (Managed Process). COBIT 2019 Design Factors show urgent areas for improvement in DF-4 (IT Related Issues), DF-6 (Compliance Requirements), and DF-7 (Role of IT). Balanced Scorecard (BSC) was also evaluated governance performance from four perspectives, financial, customer, internal process, and learning & growth, scoring 69,4% and classified as moderate. Key Performance Indicator (KPI) recommendations were also proposed, e.g., staff training increasement, operational IT services availability, user-based IT solutions, IT process measurement, security accidents reporting, effective workforce, and user-oriented IT developments. Novelty/Originality/Value: This study proposes an integrated COBIT 2019 and ITIL v4 approach, embedding good governance principles for sustainable service management in Museum Electronic-Based Government System (SPBE) and addressing the gap between governance conditions and public interests.